Preparation and Characterization of Carbon Doped ZnO and Its Effectiveness as Photocatalyst under Visible Light - Zaman, Mahbuba; Akter, Nasrin; Rahman, Md Ataur; Hossain, Md Mufazzal (Dhaka University Journal of Science, 2023)
Carbon-doped ZnO (C-ZnO) was prepared and characterized by XRD, SEM, EDX and FT-IR spectroscopy. The substitution of oxygen in the lattice of ZnO by carbon greatly extends its optical sensitivity in the visible light due to the band gap’s shrinkage, which promotes the effectiveness of electron-hole separation. SEM images showed that the surface of C-ZnO catalyst is different from that of undoped ZnO. Analysis of the elements present in the sample was done by EDX which affirms that the prepared sample contains Zn, O and C atoms. The existence of ZnO as wurtzite is confirmed by XRD analysis exhibiting little deviation of the peak position due to the presence of carbon in substitutional sites. FT-IR analysis also supports these results. Under visible light irradiation, the prepared C-ZnO shows better photocatalytic efficiency on methylene blue (MB) than un-doped ZnO. The optimum photodegradation efficiency of MB has been observed when 2 percent C-doped ZnO obtained at 300˚C calcination temperature. Dhaka Univ. J. Sci. 71(2): 127-133, 2023 (July)